2016
DOI: 10.1016/j.canlet.2016.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma patient-derived orthotopic xenografts reflect the microenvironmental hallmarks of aggressive patient tumours

Abstract: Treatment of high-risk childhood neuroblastoma is a clinical challenge which has been hampered by a lack of reliable neuroblastoma mouse models for preclinical drug testing. We have previously established invasive and metastasising patient-derived orthotopic xenografts (PDXs) from high-risk neuroblastomas that retained the genotypes and phenotypes of patient tumours. Given the important role of the tumour microenvironment in tumour progression, metastasis, and treatment responses, here we analysed the tumour m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…The role of TME, its associated cellular, non-cellular components have been well studied in detail in various types of adult-onset epithelial cancers [23,29] and some paediatric cancers such as neuroblastoma and medulloblastoma [17,36,37]. Contrarily, very few studies outline the existence of TME in RB [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The role of TME, its associated cellular, non-cellular components have been well studied in detail in various types of adult-onset epithelial cancers [23,29] and some paediatric cancers such as neuroblastoma and medulloblastoma [17,36,37]. Contrarily, very few studies outline the existence of TME in RB [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Animal procedures were performed as described previously (13,14). Briefly, 4-to-6-week-old female or male NSG mice were housed under pathogen-free conditions and received autoclaved water and food.…”
Section: Animal Proceduresmentioning
confidence: 99%
“…Briefly, 4-to-6-week-old female or male NSG mice were housed under pathogen-free conditions and received autoclaved water and food. We have previously established neuroblastoma PDOXs through the implantation of undissociated patient tumor fragments into the paraadrenal space of immunodeficient NSG mice (13,14). Established PDOXs underwent serial orthotopic transplantation into next generation NSG mice to establish up to eight in vivo generations for each PDOX model.…”
Section: Animal Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Breakeveldt N et al using neuroblastoma PDTX have reported that mice stroma recapitulate the clinical hallmarks of original primary neuroblastomas, such as the rich vascularization, macrophage infiltration, and CAF and ECM composition. Moreover, the authors observed that patientderived endothelial cells could form blood vessels, although tumor stroma was predominantly replaced with murine stroma [52]. On the same line, Sansone P et al have generated PDTX models of luminal breast cancer and isolated cancer-associated fibroblast from hormonal therapy resistant bone metastases.…”
Section: Pdtx As a Tool To Explore Microenvironmentmentioning
confidence: 99%